Severe Facio-Maxillary Injury Resulting from Camel Bite - J. K. Sinha; A. B. Srivastava (Indian Journal of Plastic Surgery)
A rare case of severe facio-maxillary injury resulting from a camel bite is described. Simple procedure like interdental islet wiring can give gratifying results.